Management of Emergency Department Overcrowding (EDOC) in a teaching hospital. - Nik Azlan NM,; Ismail MS,; Azizol M, (Penerbit UKM, 2013)
Emergency Department Overcrowding (EDOC) has been a longstanding problem. It is defined as a situation where the demand for emergency services exceeds the ability of an Emergency Department (ED) to provide quality care within appropriate time frames. Hospital beds closure or access block to ward admission is one of the most important cause of Emergency s e.g. disaster. A surge response entails even greater responses including implementing Department overcrowding. This could be compounded further in events of a patient surge eg affirmative measurement in order to mitigate the issue in tackling the situation. The steps in managing EDOC were: 1. Recognizing EDOC, 2. Initiating action, 3. Maintaining patient flow, 4. Setting clinical goals and 5. Deploying a Surge Team for Advance Triage or Fast Tract.